Protein phosphatase 2A-B55δ enhances chemotherapy sensitivity of human hepatocellular carcinoma under the regulation of microRNA-133b. Issue 1 (December 2016) - Zhuang, Qunying; Zhou, Tengjian; He, Chengyong; Zhang, Shili; Qiu, Yang; Luo, Bing; Zhao, Ran; Liu, Hengchuan; Lin, Yuchun; Lin, Zhongning
Abstract Background Hepatocellular carcinoma (HCC) remains a major public health problem worldwide. The identification of effective chemotherapeutic targets for advanced HCC patients is urgently required. In this study, we investigated the role of protein phosphatase 2A-B55δ subunit (PP2A-B55δ, encoded by thePPP2R2D gene) and related mechanisms affecting chemotherapy sensitivity of HCC. Methods Experimental approaches for measuring the levels ofPPP2R2D mRNA and B55δ protein in HCC included bioinformatics analyses, quantitative real-time polymerase chain reaction (qRT-PCR), western blotting (WB), immunofluorescence and immunohistochemistry assays. Cell cycle, migration, colony formation, apoptosis, and cell proliferation assays in stablePPP2R2D -knockdown and -overexpression cell linesin vitro, and tumorigenicity assaysin vivo, were performed to explore the function of B55δ in cisplatin (cDDP) chemotherapy of HCC. Bioinformatics prediction, luciferase reporter assays, qRT-PCR, WB, and cell cycle analyses were used to reveal the regulatory relationship between microRNA-133b (miR-133b) andPPP2R2D expression. miR-133b mimic and inhibitor were used to elucidate the regulatory mechanism. Results Our studies showed thatPPP2R2D expression was down-regulated in both HCC tumors and HCC cell lines. Treatment with cDDP increased the amount of B55δ protein. Artificially increasing the expression of B55δ counteracted cyclin-dependent kinase 1 activation, modulated transitions of the cell cycle, and increased the suppressive effect of cDDP on cell migration, colony formation, apoptosis, and proliferationin vitro and tumor growthin vivo, thus enhancing therapeutic efficiency. In contrast, knockdown of B55δ partially inhibited the effect of cDDP chemotherapy. miR-133b was shown to regulatePPP2R2D expression by binding to the 3'-untranslated region ofPPP2R2D mRNA. The miR-133b/PPP2R2D signaling pathway affects the effectiveness of cDDP chemotherapy. Conclusions PP2A-B55δ, regulated by miR-133b, enhances the sensitivity of HCC to cDDP chemotherapy. Our data indicate that PP2A-B55δ might be a novel and attractive target for increasing chemotherapy sensitivity of HCC.